Digital Payment Integration in Accounting Information Systems to Support MSMEsRevitalization in Bali: A Literature Review - Gita Apsari Dewi; Permana, Dewa Gde Yoga; A.A. Gde Agung Nanda Perwira (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2025)
MSMEs are a cornerstone of Bali’s economy, relying heavily on local cultural strengths and tourism as the main attraction. The decline in tourist numbers due to the pandemic has necessitated adaptive revitalization strategies aligned with technological developments, including the digitalization of payments. Previous literature indicates that QRIS (Quick Response Code Indonesian Standard) can enhance transaction efficiency and MSME revenue; however, few studies have explored integrating these transaction data into Accounting Information Systems (AIS) to support strategic decision-making within the context of Balinese culture.This study employs a systematic literature review (SLR) to identify findings, gaps, and development opportunities from relevant studies published over the last five years. The analysis shows that integrating QRIS with AIS can produce accurate, real-time, and transparent financial data flows, facilitating reporting, cost control, and business planning. Such integration also has the potential to optimize the competitiveness of Bali’s tourism-based MSMEs by considering cultural factors, such as the Tri Hita Karana values and the banjar social structure, which influence technology adoption. The study concludes that successful implementation requires supporting infrastructure, digital literacy, and policies aligned with the local socio-cultural context.